Establishment of a leucine-based poly(ester amide)s library with self-anticancer effect as nano-drug carrier for colorectal cancer treatment - Tong, Tong; Chen, Lezong; Wu, Siying; Cao, Zhong; Song, Yuanbin; Wu, Jun (Chinese chemical letters, 2024)
Colorectal cancer is a common cancer worldwide. Traditional chemotherapeutic drugs often face limitations such as poor aqueous solubility and high systemic toxicity, which can lead to adverse side effects and limited therapeutic efficacy. In this study, a library of one kind of biodegradable and biocompatible polymer, leucine based-poly(ester amide)s (Leu-PEAs) was developed and utilized as drug carrier. The structure of Leu-PEAs can be tuned to alter their physicochemical properties, enhancing drug loading capacity and delivery efficiency. Leu-PEAs can self-assemble into nanoparticles by nanoprecipitation and load paclitaxel (PTX) with the diameter of ∼108 nm and PTX loading capacity of ∼8.5%. PTX-loaded Leu-PEAs nanoparticles (PTX@Leu-PEAs) demonstrated significant inhibition of CT26 cell growth in vitro. In vivo, these nanoparticles exhibited prolonged tumor accumulation and antitumor effects, with no observed toxicity to normal organs. Furthermore, blank Leu-PEAs nanoparticles also showed antitumor effects in vitro and in vivo, which may be attributed to the activation of the mammalian target of rapamycin (mTOR) pathway by leucine. Consequently, this biocompatible Leu-PEAs nano-drug delivery system shows potential as a promising strategy for colorectal cancer treatment, warranting further investigation. A PTX loaded nanoplatform based on Leu-PEA polymers (PTX@4L6 NPs) is prepared by nanoprecipitation and it induces tumor cells apoptosis via efficient PTX loading and its self-anticancer effect. [Display omitted]